PENGARUH PERBESARAN LUAS ELEKTRODA TERHADAP PROBABILITAS TEGANGAN TEMBUS PADA DIELEKTRIK UDARA MENGGUNAKAN TEGANGAN TINGGI DC - Fianto, Aulia Ramadhan; Dhofir, Moch.; Hasanah, Rini Nur (Jurnal Mahasiswa TEUB, 2024)
Breakdown voltage can be a random phenomenon that can cause electrical damage, especially DC electric power systems which are being developed because they have advantages over AC electric power systems. One of the components in an electric power system is a conductor wire with a small resistance value which can reduce power losses. One way to reduce the resistance value is to increase the cross-sectional area of the conducting wire, which can also be called the law of area enlargement. This research will describe the effect of increasing the electrode area on the probability of breakdown voltage in air dielectrics using high DC voltage. Leakage current data collection is needed to obtain the air resistance value at each electrode magnification and breakdown voltage data collection using the up and down method is carried out at the High Voltage Laboratory, Department of Electrical Engineering, Faculty of Engineering, Brawijaya University. Electric field simulations were carried out using FEMM 4.2 software with varying magnification of electrode areas A, 2A, 3A, 4A, and 5A. Keywords - Enlarging of Area, electrode, breakdown voltage, high voltage DC